Revealing Mucilage Event-Linked Community Composition in the Sea of Marmara from eDNA Metabarcoding Data - Melek İşinibilir; Raşit Bilgin; Anıl Doğan Örün; Onur Doğan (Aquatic Sciences and Engineering)
Mucilage events are among the most conspicuous phenomena in marine ecosystems and present numerous challenges in determining the composition of communities associated with them. To overcome this problem, we used environmental DNA (eDNA) metabarcoding approaches to reveal the species-level resolution of community composition. Mucilaginous aggregates were sampled at six collecting sites during a novel mucilage event (autumn 2021–summer 2022) in the Sea of Marmara, Türkiye. A wide range of plankton community compositions was detected in mucilage samples. eDNA metabarcoding was effective in predicting the community composition of mucilage, which is composed of a wide variety of organisms from mucilaginous aggregates.